DOCUMENTS OF THE REGIONAL ARCHIVES OF THE EUROPEAN RUSSIA FOR STUDYING EXILE OF PEOPLE FROM THE NORTH-EASTERN CAUCASUS IN THE SECOND HALF OF THE XIX - EARLY XX CENTURY: HISTORIOGRAPHY AND RESEARCH EXPERIENCE - Krasin, V M (History, Archeology and Ethnography of the Caucasus, 2015)
The author of the article reviews all known publications, in a varying degree concerning the exile from the North-East Caucasus in the second half of the 19th-early 20th centuries, which were prepared using documents of regional archives of Europea n Russia. The author outlines some promising directionsin the use of the documents of regional archives of European Russia in the study of the mentioned problem. The article presents the list of funds with the largest number of documents on the exile from the North-East Caucasus in the second half of the 19th-early 20th centuries.
Keywords: North-Eastern Caucasus; administrative exile; police supervision